Improved oxidation resistance through an in-situ formed diffusion barrier: Oxidation behavior of amorphous multi-component FeCrAlMoSiY-coated Zr in high-temperature steam. (15th August 2021) - Li, Yuhang; Meng, Fanping; Ge, Fangfang; Huang, Feng
Highlights: A novel multi-component amorphous FeCrAlMoSiY coating. Oxidation resistance in 1200 °C steam of the specimen was improved. Retarded coating-substrate interdiffusion by the in-situ formed Si-Zr layer. Protective α-Al2 O3 scale acts as a barrier to inhibit severe oxidation. Abstract: Long-term reliability of some systems for high-temperature applications has been hindered by intensive coating-substrate interdiffusion. Herein, we report a novel column-free multi-component FeCrAlMoSiY coating sputtered on zircaloy. During the 1200 °C steam oxidation, the Si atoms preferentially migrated to the coating-substrate interface to form a continuous Zr2 Si-rich diffusion barrier to inhibit both inward diffusion of the coating and outward of substrate elements. Therefore, the formation of protective α-Al2 O3 scale has been promoted, which effectively prevented the underlying coating and substrate being oxidized. Formation of the in-situ diffusion barrier and oxidation protection mechanisms of this coating were then discussed.